2020
DOI: 10.3390/joitmc6040154
|View full text |Cite
|
Sign up to set email alerts
|

Configuring the Drivers and Carriers of Process Innovation in Manufacturing Organizations

Abstract: In today’s hyper-competitive manufacturing world, the rapidly changing landscape has put new demands on organizations, and they need to reinvent themselves by injecting new strategies in order to stay ahead of the competition. Therefore, to achieve world-class performance and competitiveness in the global environment and competition, there is immense pressure on manufacturing organizations with limited resources to invariably pursue main drivers to enable them to improve process innovation. In this backdrop, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 81 publications
(144 reference statements)
0
14
0
Order By: Relevance
“…The sustainable accomplishment of enterprises asks for a vigorous harmonizing of organizational ambidexterity and product innovation [22]. In order to enhance process and product innovation, Ali et al [23] suggests that manufacturing firms need to rely on executing efficient human resource management practices by providing conversant training to their staff, refining work skills and commitment by the suitable compensation system and furthering organizational culture. Considerable research efforts by different researchers have been dedicated to recognize and elaborate the factors that results in organizational ambidexterity.…”
Section: Contextual Ambidexterity and New Product Innovation Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sustainable accomplishment of enterprises asks for a vigorous harmonizing of organizational ambidexterity and product innovation [22]. In order to enhance process and product innovation, Ali et al [23] suggests that manufacturing firms need to rely on executing efficient human resource management practices by providing conversant training to their staff, refining work skills and commitment by the suitable compensation system and furthering organizational culture. Considerable research efforts by different researchers have been dedicated to recognize and elaborate the factors that results in organizational ambidexterity.…”
Section: Contextual Ambidexterity and New Product Innovation Outcomesmentioning
confidence: 99%
“…Contextual ambidexterity has made business units proficient of incorporating new practices or system for radical innovation and the competence and invention essential for incremental innovation. Ali et al [23] inspected the degree to which illustrative policies are implemented by manufacturing enterprises and their influence on the extents of product innovation. It is suggested that management should get themselves acquainted with the novel strategies that augment operational performance and enable effective decisionmaking.…”
Section: Contextual Ambidexterity and New Product Innovation Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pro-ecological strategy context, failure and instability occur when there is a dissonance between the announced strategy and its execution. Employees and customers are very much aware of the need for conservation and sustainability and they lose their trust if such phenomena appear [48,49].…”
Section: Organization Culturementioning
confidence: 99%
“…To avoid anarchy in an organization, there have to be common goals and values shared among team members. Another condition is to keep coherence between management style and organizational culture [49,123]. In the directive style, there is no place for flexibility and freedom in implementing the management style.…”
mentioning
confidence: 99%